Resilience of Muslim Families in the Pandemic Era: Indonesian Millennial Muslim Community's Response Against COVID-19 - Abdurrohman Kasdi; Saifudin Saifudin (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
This paper aims to investigate the resilience of millennial Muslim families in Indonesia in the face of the COVID-19 outbreak. The indicators examined were their resilience in gender partnerships, health and security, economic conditions, social-psychological resilience, and social-cultural resilience. The sample of data used in this study were 403 respondents. This research is a quantitative descriptive. The SPSS tool is used to describe the percentage of respondents' answers. The results showed that the gender partnership, health and safety, psychological social resilience, and socio-cultural resilience were in a quite good condition, but the economic conditions of the millennial Muslim family were the opposite. Family science practitioners can estimate millennial Muslim family behavior after the COVID-19 pandemic through this article. As for academics, this article is used for further research by integrating millennial Muslim family endurance. Empirically this research is useful to increase understanding of family resilience in the face of crisis. Millennial Muslim family resilience is a relatively new phenomenon for practitioners and academics. This research is a preliminary study that investigates the resilience of millennial Muslim families. Therefore, this investigation will serve as an investigation of knowledge about the resilience of millennial Muslim families when a virus outbreak occurs in Indonesia and the world.